Control interno y la optimización de la gestión del riesgo en la Cooperativa de Ahorro y Crédito Alli Trpuk Ltda, 2018 - Yessenia, Salinas (2021)
ABSTRACT The evaluation of Internal control is a detailed review that is carried out to an entity on essential aspects such as financial and administrative management to determine that the processes and resources are used correctly through risk management. It can be identified, analyze, and respond to risk factors. The purpose of this research was to evaluate the internal control and optimization of risk management in the Cooperativa de Ahorro y Crédito Alli Tarpuk LTDA, 2018. For this, it was started from the identification of the study problem. Clearly defining the objectives both general and based on the theoretical aspects regarding the research topic, an interview, surveys, and the COSO ERM internal control evaluation model of 2017 were applied, evaluating each of the principles and components that characterize it. The results revealed by the Cooperative are that requires the Board of Directors and Surveillance to participate continuously, intervening in the active part in the case of the credit area. It does not have a code of ethics. There are shortcomings in the area of physical security and electronics. They do not have a risk map; the work environment is not evaluated, that is why it is recommended to comply with the suggestions made during the development of the research project to help mitigate the risks that arise within each Cooperative area. Key Words: Internal Control, Risk Management, COSO ERM. Reviewed by: Mgs. Marcela González Robalino English Professor c.c. 0603017708